Therapeutic Management of Hypothenar Hammer Syndrome Causing Ulnar Nerve Entrapment. (12th May 2010) - Cigna, Emanuele; Spagnoli, Anna Maria; Tarallo, Mauro; De Santo, Liliana; Monacelli, Giampaolo; Scuderi, Nicolò
Abstract : Introduction . The hypothenar hammer syndrome is a rare traumatic vascular disease of the hand. Method and Materials . We report the case of a 43-years-old man with a painful tumefaction of the left hypothenar region. The ulnar artery appeared thrombosed clinically and radiologically. The patient underwent surgery to resolve the ulnar nerve compression and revascularise the artery. Results . The symptoms disappeared immediately after surgery. The arterial flow was reestablished. Postoperatively on day 20, a new thrombosis of the ulnar artery occurred. Conclusion . Hypothenar hammer syndrome is caused by repetitive trauma to the heel of the hand. The alterations of the vessel due to its chronic inflammation caused an acute compression of the ulnar nerve at the Guyon's canal and, in our case, do not allow a permanent revascularisation of the ulnar artery.